Changes in the composition of the fauna associated with the cassava mealybug, Phenacoccus manihoti, following the introduction of the parasitoid Epidinocarsis lopezi - Neuenschwander, Peter; Hammond, W.N.O.; Hennessey, R.D. (Springer, 1987)
Over 130 species of insects were found in association with the cassava mealybug (CM), Phenacoccus manihoti, and its newly introduced parasitoid Epidinocarsis lopezi in Africa. As the CM in SW Nigeria declined under the influence of E. lopezi, this introduced wasp maintained densities of 2.8-3 per CM-infested tip early in the dry season and 1.3-1.6 per infested tip late in the dry season, but declined overall from 1.3 to 0.2 per randomly collected tip within 1 year. The decline of CM led to a sharp reduction in numbers of indigenous coccinellids, particularly of Hyperaspis spp. and to a lesser extent of Exochomus sp., due to competition with E. lopezi for the common food source. Numerous species of other polyphagous predators and parasitoids of coccinellids were found in low numbers. Indigenous primary parasitoids, Anagyrus spp., were rare, but their 10 spp. of hyperparasitoids were often reared from E. lopezi, with Prochiloneurus spp. and Chartocerus spp. being the most common. Hyperparasitism declined from 41.3% in March 1983 to 16.9% in Dec 1984 and proved to be positively density-dependent. The effects of hyperparasitoids on this biological control programme are discussed.